Exfoliation, reduction, hybridization and polymerization mechanisms in one-step microwave-assist synthesis of nanocomposite nylon-6/graphene. (20th June 2018) - González-Morones, Pablo; Hernández-Hernández, Ernesto; Fernández-Tavizón, Salvador; Ledezma-Rodríguez, Raquel; Sáenz-Galindo, Aide; Cadenas-Pliego, Gregorio; Ávila-Orta, Carlos A.; Ziolo, Ronald F.
Abstract: Few if any reports exist that elucidate the phenomena that take place in the microwave-assist polymerization (MAP) of heterogeneous multi-component systems to form polymer nanohybrid composites. We elucidate the four distinct steps that take place during the in-situ MAP of Nylon-6 from ε-caprolactam and 6-aminocaproic in the presence of graphite oxide (GrO), which results in the formation of a reduced graphene oxide Nylon-6 nanohybrid in a one-step synthesis; exfoliation, reduction take place in <60 s; polymerization occurs after 60 s; hybridization during both periods. An increase in molecular weight and conversion of non-grafted Nylon-6 during hybridization takes place unlike in conventional in-situ polymerizations of Nylon-6/GrO where reduction of the MW is observed. It is also shown for the first time that the crystallization of grafted Nylon-6 in the hybrid exists in both α and γ phases. The grafted molecules represent 50 wt % of the hybrid. Graphical abstract: Image 1 Highlights: Phenomena of the MAP of a heterogeneous multi-component system to form PNHC were elucidated. A timeline was established for the exfoliation, reduction, polymerization and hybridization. MAP was explained by initial dielectric heating of graphite oxide. Graphite oxide and microwave parameters control nylon molecular weight. Crystalline polymer nanohybrids of Nylon-6 and GrO can be obtained using MAP.